Knee Pain During Islamic Prayer after Anterior Cruciate Ligament Reconstruction Using Hamstring and Bone Patellar Tendon Autograft - N., Ahmed; M.T., Shihabudin; S., Ab Rahman (IIUM Medical Journal Malaysia, 2020)
Introduction: Hamstring tendon (HT) and bone patellar tendon bone (BPTB) are the commonly used autograft in an anterior cruciate ligament reconstruction surgery. The BPTB is said to have more incidence of anterior knee pain compared to HT. The study aimed to compare the severity of knee pain during Islamic prayer kneeling. Methods: A cross sectional cohort analysis of patients undergoing ACL reconstruction surgery using BPTB with HT autografts was conducted to determine differences in postoperative pain while kneeling and ability to pray in normal position. Kneeling during prayer and the ability to sit while performing prayer were assessed at 3rd, 4th, 5th and 6th month. Results: There were no significant differences in mean pain score while kneeling at 3rd, 4th, 5th and 6th month. The mean difference of patient’s ability to perform normal prayers for BPTB (3.56+1.16) and HT (3.30+1.05) was found insignificant. The average number of patients in both groups was able to pray between 3 to 4 months post operatively as full range of motion of knee is allowed within this period. Total 49 patients (BPTB 23, HT 26) out of 60 were able to pray normally within 4 months post-operation. Mostly delayed due to anterior knee pain. Conclusion: There is no different in term of knee pain during kneeling while performing Islamic prayer between those who had their ACL reconstructed either using BPTB or HT autograft.